Analysis of the Comparison Between Noise Levels and Vehicle Volume on the Section of Jalan Pahlawan Sidoarjo to Jalan Raya Legundi Krian - Rifqi Hanan; Wibisana Hendrata (Syntax Corporation Indonesia, 2023)
Analysis of the comparison of noise levels with vehicle volume levels on Jl. Pahlawan Sidoarjo to Jl. Raya Legundi Krian. Kali Porong is used as a mud sewer for Lapindo to prevent damage to the mud retaining embankment. Lapindo's continuous mud disposal causes sedimentation in Porong River. The mud does not settle much along the river, but settles in the estuary of Kali Porong in the Madura Strait due to the flow of Lapindo mud and sediment transport from Kali Porong to the estuary and along the coast. This study suggests using Landsat 8 satellite images with the H. Wibisana (2021) algorithm to calculate Total Suspended Solid (TSS) levels. The results showed that the algorithm had a better correlation coefficient in 2018 (49.72%) and 2019 (69.065%). In 2020 and 2022, the Guzman-Santella (2009) algorithm gave the best results with correlation coefficients of 84.297% and 64.18%, respectively. In 2023, Ety Parvati's (2014) algorithm has a correlation coefficient of 79.18%. This research can be a reference for future research and help map the distribution of TSS and monitor changes in TSS. This will provide appropriate solutions in decision-making related to environmental impacts and development around the area.